A review of peer-assisted learning to deliver interprofessional supplementary image interpretation skills. Issue 1 (September 2017) - Bain, P.; Wareing, A.; Henderson, I.
Abstract: Background: Peer-assisted learning provides a means through which individuals can learn from one another through a reciprocal process. Radiographic image interpretation skills are fundamental to both diagnostic radiography students and medical students due to their shared role in preliminary evaluation of conventional radiographic images. Medical students on graduation, may not be well prepared to carry out image interpretation, since evidence suggests that they perform less well than radiographers in e.g. Accident and Emergency situations. Method: A review of literature was conducted exploring the application of peer-assisted learning within diagnostic radiography and health education more widely as well as the practice of initial image interpretation. An extensive and systematic search strategy was developed which provided a range of material related to the areas. Findings: An overview was obtained of the effectiveness of peer-assisted learning and the issues associated with development of image interpretation skills and a degree of discrepancy was identified between the two cohorts regarding their interpretative competence and confidence. This inconsistency may create an opportunity to apply peer-assisted learning, better preparing both disciplines for the practical application of image interpretation skills. Conclusion: The review identified the lack of a substantial evidence base relating to peer-assisted learning in radiography. Peer-assisted learning is not widely embraced in an interprofessional context. Multiple positive factors of such an intervention are identified which outweigh perceived negative issues. Student teacher and learner may benefit as should the clinical service from enhanced practitioner performance. The findings justify further research to develop the evidence base. Highlights: Many diagnostic radiographers and medics are involved in image interpretation. Evidence indicates an imbalance in image interpretation competence and confidence. Practice of peer-assisted learning is novel within radiography education. A range of potential benefits concerning peer-assisted learning are identified. Peer-assisted learning could provide a platform to improve interpretation skills.